Description of a new flower fly species of the Copestylum vagum group (Diptera: Syrphidae) from pristine Amazonian rainforests of Colombia and Suriname - Montoya, Augusto León; Parada-Marín, Henry Mauricio; Ramos-Pastrana, Yardany (Zootaxa, 2022)
The adult stage of a new flower fly species, Copestylum enriquei sp. nov. (Diptera: Syrphidae) is described based on a single male collected in pristine rainforest in the Amazonian region of Colombia (type-locality: Florencia, Caquetá) and two females from a conserved forest in Suriname (Para and Brokopondo). Copestylum enriquei sp. nov. belongs to the C. vagum species group and is similar in appearance to Copestylum vagum (Wiedemann), C. musicanum (Curran), C. tenorium Ricarte & Rotheray, and C. chapadensis (Curran) from which it differs by the gena and face separated by a very broad brown vitta; scutum orange except for the wide medial vitta, which is dark and metallic, ending before the prescutellar region, with the apical margin M-shaped; tibiae dark-brown, except yellow on basal 1/4. The male genitalia of C. enriquei sp. nov. are unique and striking among the C. vagum species group, characterized by the epandrium and cercus black, contrasting with the colour of hypandrium and surstylus, which are orange; epandrium with a dorsal extension, a novel character among this species group, in addition to the L-shaped surstylus, with two pairs of rounded ridges in the dorsal edge, similar to a small deer antler in velvet. Images of type material, including photographs of male genitalia are provided. A comparison of the diagnostic characters is provided as well as modifications to the previous keys to distinguish C. enriquei sp. nov. from the other species of the C. vagum group. The species Copestylum araceorum Ricarte & Rotheray and C. tenorium Ricarte & Rotheray are recorded for the first time in the Amazonian rainforest in Colombia.